THE EFFECT OF IMAGE, PROMOTION, COMMUNICATION, AND FACILITIES ON SENIOR HIGHT SCHOOL STUDENT’S INTEREST - Ibrahim, Gafaruddin; Hamidah, Hamidah (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2017)
The research data is obtained trough questioners from 320 students senior high school and vocational school around the campus of STIKOM MuhammadiyahBatam. This analysis of the units by using research of associative quantitative model of multiple correlation which test the result of calculation data obtained that fourth variable; image, promotion, communication, and facilities together have a significant effect on students interest to STIKOM MuhammadiyahBatam. there is a positive direct effect of image on the interest of students of Senior High School entrance into STIKOM MuhammadiyahBatam City, if the value of t_hitung>t_table, From the analysis results can be compared that the value t_hount>t_table (14.771> 1.976) ,. The result of analysis obtained t_hitung equal to 10,071 bigger value with t_tabel value equal to 1,976, 10,071> 1,976, hence decision taken is there is direct positive influence of promotion to interest of student of School of Advanced Up. The result of analysis obtained t_count 4,271 value bigger when compared with t_table value equal to 1,976, 4,271> 1,976, hence decision taken is there is positive direct influence of communication to student interest value of F_count equal to 2245.199 bigger when compared with value of F_table 2,400 ( 2245.199> 2.400), The conclusion by increasing image, promotion, communication, and facilities will increase students interest to STIKOM MuhammadiyahBatam can be increased by effort of image, promotion, communication, and facilities. Keywords: Interest, Image, Promotion, Communication And Facilities